Sweden : Financial Sector Assessment Program Update: Technical Note on Contingency Planning, Crisis Management and Bank Resolution. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This abstract reviews the recommendations made in the FSAP Update for Sweden in the areas of contingency planning, crisis management, and bank resolution. Although Sweden crisis management fared well during the global financial crisis, its authorities are reviewing the framework for managing financial crises to incorporate crisis lessons. They recommend a domestic institutional framework, an effective cross-border cooperation, an emergency liquidity assistance (ELA), a deposit guarantee scheme (DGS), and state support to systematically important financial institutions (SIFIs).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet